“Rugged Vaginas” and “Vulnerable Rectums”: The Sexual Identity, Epidemiology, and Law of the Global HIV Epidemic - Ahmed, Aziza (Columbia Journal of Gender and Law, 2013)
AIDS remains amongst the leading causes of death globally. Identity is the primary mode of understanding HIV and organizing in response to the HIV epidemic. In this Article, I examine how epidemiology and human rights activism co-produce ideas of identity and risk. I call this the “identity/risk narrative”: the commonsense understanding about an identity group’s HIV risk. For example, epidemiology offers the biological narrative of risk: anal sex and the weak rectal lining make men who have sex with men more vulnerable to HIV; while the fragility of a woman’s vaginal wall provides a biological foundation for women’s vulnerability. These biological narratives underpin rights-claiming in international human rights institutions: many women’s rights activists and gay rights activists rely on these biological ideas of risk to define their groups and demand legal and policy change. The corresponding legal projects emanate from identity driven projects.